Effects of Vitamin D Deficiency on the Function of the Cardiac Autonomic Nervous System in Rats - Xuemei Luo; Jie Xiong; Hong Cai; Runmei Zou; Fang Li; Yuwen Wang; Cheng Wang (Hindawi-Wiley, 2022)
Background. Previous studies have shown that autonomic nervous system (ANS) dysfunction was closely related to vitamin D (VD) deficiency, but the mechanism remained unclear. The purpose of this study was to evaluate the mechanism of VDdef on the function of cardiac ANS in rats. Methods. After 10 weeks of VD deficiency feeding, we successfully established a VD-deficient rat model. The body weight of rats was recorded, and the levels of calcium (Ca), phosphorus (P), creatinine (CRE), triglyceride (TG), hemoglobin (HG), and 25(OH)VD3 in serum were detected by corresponding kits. Short-time frequency domain analysis was used to evaluate the heart rate variability (HRV) of all rats. The expression of tyrosine hydroxylase (TH) in the atria and ventricle were detected by IHC. ELISA was used to determine the levels of acetyl choline (Ach) and nitric oxide (NO). HPLC was used for the detection of norepinephrine (NE). The expressions of KIR3.1, HERG, KVLQT1, and Mink were detected by qRT-PCR and western blot. Results. After 10 weeks of VD deficiency feeding, serum 25(OH)VD3 levels were markedly reduced in the VDdef group, and sera Ca and P, as well as body weight, were notably decreased in the VDdef group. In resting and motion states, VD deficiency resulted in a decline in HF levels and a mark increase in VLF and LF/HF levels. VD deficiency caused a reduction in the release of the local cardiac neurotransmitters TH and Ach. NE and NO levels were also remarkably depressed in the VDdef group. In addition, VD deficiency resulted in severely impaired expression of potassium channel proteins. Conclusion. VD deficiency leads to cardiac ANS dysfunction. The imbalance in heart rate variability, impaired release and secretion of neurotransmitters and local plasma hormones in the heart, and downregulation of potassium channel protein expression caused by VD deficiency may be closely related to this dysfunction.